Acidosis of severe falciparum malaria: heading for a shock? - Maitland, K; Newton, C (2005)
Severe Plasmodium falciparum malaria encompasses a complex syndrome affecting many organs and causing physiological perturbations that have many features in common with children with sepsis. Among these, metabolic acidosis has emerged as a central feature of severe malaria and is the best independent predictor of a fatal outcome in both adults and children. There is now clear evidence that intravascular hypovolaemia (shock) is common in children with malarial acidosis. How it should be treated presents a therapeutic dilemma because acidosis often coexists with impaired consciousness (cerebral malaria). We summarize the results of recent clinical trials examining the safety and efficacy of volume expansion in children with 'cerebral malaria' complicated by acidosis.